Presence of polioviruses and other enteral viruses in sewage: a survey in the Czech Socialistic Republic 1969-1976 - Zdrazílek, J; Drasnar, M; Hlavová, H; Jadrnícková, E; Jandásek, L; Kasová, V; Koza, J; Matyásová, I; Uvízl, M; Valihrach, J; Weigendová, J (Journal of hygiene, epidemiology, microbiology, and immunology, 1982)
Monitoring polioviruses in sewage is a permanent task within the poliomyelitis vaccination control programme in Czechoslovakia. The results of sewage examination in certain localities of the CSR in the years 1969 to 1976 are reported. During the study years, nearly 3600 samples of sewage were examined. The yield was about 9 percent of samples positive for polioviruses and 22 per cent of samples positive for other viruses. The virus positivity rate was roughly the same in samples from municipal sewers and samples from children's facilities. The majority of polioviruses were detected within 3 to 4 months after mass vaccination campaigns, which in Czechoslovakia are carried out in spring. In some years types 2 and 3 polioviruses tended to occur in later months after vaccination as well. Antigenic characterization of the polioviruses isolated in Prague showed that polioviruses possessing an rct+ marker and antigenically related but not identical with the original vaccine strains were sometimes present late during the intervals between vaccination campaigns. It may be assumed that vaccine strains which have been in circulation for sufficiently long time are subject to a gradual change or that vaccine-like strains have been imported.